1980
DOI: 10.1063/1.91876
|View full text |Cite
|
Sign up to set email alerts
|

Backward wave oscillation in the gyrotron

Abstract: The electron cyclotron maser instability is shown to support backward wave oscillation in a traveling-wave gyrotron. Numerical values for two parameters that identify oscillation thresholds are determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Meanwhile, the start oscillation condition of the gyro-BWO was also derived to exploit the backward wave oscillations as tunable millimeter wave sources. 14,15 The theoretical analysis was extended by considering the mismatch reflections at both ends of the beam-wave interactions to compare the linear properties of the conventional gyro-BWO and the reflective type gyro-BWO. 16 The backward wave oscillation was explicitly treated as an absolute instability occurring in a finite length ECM system by Lin and Kaw.…”
Section: Linear Stability Properties: Absolute Instabilities In Amentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the start oscillation condition of the gyro-BWO was also derived to exploit the backward wave oscillations as tunable millimeter wave sources. 14,15 The theoretical analysis was extended by considering the mismatch reflections at both ends of the beam-wave interactions to compare the linear properties of the conventional gyro-BWO and the reflective type gyro-BWO. 16 The backward wave oscillation was explicitly treated as an absolute instability occurring in a finite length ECM system by Lin and Kaw.…”
Section: Linear Stability Properties: Absolute Instabilities In Amentioning
confidence: 99%
“…Following experiments with moderate energy electron beam and high energy electron beam were performed to obtain kilowatt-level 2,8-10 to megawatt-level [11][12][13] millimeter wave sources, but the fast tuning bandwidth was less than expected. Theoretical and simulation works were then motivated by experiments for studying the essential properties of gyro-BWO, e.g., the start oscillation criteria (linear properties), [14][15][16] the saturation efficiency of the beamwave interaction, [17][18][19][20][21][22][23] and the nonstationary oscillation of the gyro-BWO (nonlinear properties). 24,25 The theoretical analysis and numerical simulation formed the basis of the experimental design and have been extensively applied on the study of the efficiency enhancement of gyro-BWO induced by the magnetic field tapering 18,19,21 or the tapering of waveguide wall radius.…”
Section: Introductionmentioning
confidence: 99%
“…1 Start oscillation conditions were analyzed using the linear theory. [2][3][4] Nonlinear analysis revealed that properly tapering the magnetic field can enhance the efficiency of the gyro-BWO from 10-15% to 25-30%. 5 An experiment with a down tapered interaction structure could achieve a peak power of a factor of 2, i.e., higher than that of a uniform tube.…”
Section: Introductionmentioning
confidence: 98%
“…12,13 Either cylindrical or rectangular waveguides are usually used as the interaction structures of gyro-BWOs. [1][2][3][4][5][6][7][8][9][10][11][12][13] Various transverse waveguide modes may be resonantly excited by matching the beam-wave resonance condition when the beam current exceeds their start-oscillation currents.…”
Section: Introductionmentioning
confidence: 99%
“…The dispersion relation is usually used to predict the growth rate of the forward amplifying wave, but cannot determine the axial field profile, the launching loss, or the onset of self-excited oscillations in a waveguide of finite length. To analyze all these issues, the dispersion equation should be solved together with the boundary conditions as it was done for the linear-beam backward-wave oscillator ͑BWO͒ by Johnson 20 and for the gyro-BWO by Wachtel and Wachtel 21 and Saito et al 22 Although a self-consistent nonlinear code with the particle-tracing technique 19 can also be used to determine the linear behavior of coaxial gyro-TWTs, the process of searching for a solution consumes considerable time. Therefore, an efficient analytical model is required to support the preliminary design of a coaxial gyro-TWT.…”
Section: Introductionmentioning
confidence: 99%